ENVIRONMENTAL ISSUES IN MINING MANAGEMENT - Nurhayanti, Nurhayanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Many countries are faced with environmental problem soil, water, air, erosion, critical land, environmental pollution, floods and droughts. The increasingly worrying environmental support problems are actually caused by unwilling environmental damage that has made the conditions of human habitat more and more worrying. In practice, the realization of mining management makes the conditions of human habitat increasingly worrying. The activity of this sector has been caused by a lack of environmental problems. Some of the negative impacts caused by mining activities are, among others, the rate of deforestation (decrease in the amount of covered forests) and damage to land that increasingly disrupts the existing ecosystem order, damage to the infrastructure in the mining area, loss of resilience and supporting capacity of the living environment leading to a variety of natural disasters, tenurial conflicts, the potential for criminalization of indigenous communities around mining sites, as well as other negative effects.Keywords: environmental damage, rules, licenses